Re-imagining Ukrainian Canadians : history, politics, and identity - Mochoruk, Jim, 1957-; Hinther, Rhonda L., 1974- (Toronto [Ont.] : University of Toronto Press, 2011)
Ukrainian immigrants to Canada have often been portrayed in history as sturdy pioneer farmers cultivating the virgin land of the Canadian west. The essays in this collection challenge this stereotype by examining the varied experiences of Ukrainian-Canadians in their day-to-day roles as writers, intellectuals, national organizers, working-class wage earners, and inhabitants of cities and towns. Throughout, the contributors remain dedicated to promoting the study of ethnic, hyphenated histories as major currents in mainstream Canadian history. Topics explored include Ukrainian-Canadian radicalism, the consequences of the Cold War for Ukrainians both at home and abroad, the creation and maintenance of ethnic memories, and community discord embodied by pro-Nazis, Communists, and criminals. Re-Imagining Ukrainian-Canadians uses new sources and non-traditional methods of analysis to answer unstudied and often controversial questions within the field.
Introduction / Jim Mochoruk and Rhonda L. Hinther -- Part one: New Approaches to Old Question -- Generation gap: canada's postwar ukrainian left / Rhonda L. Hinther -- Locating identity: the Ukrainian cultural heritage village as a public history text / Karen Gabert -- "A vaguely divided guilt": the aboriginal Ukrainian / Lindy A. Ledohowski -- Part two: Leaders and Intellectuals -- "Great tasks and a great future": Paul Rudyk, pioneer Ukrainian Canadian entrepreneur and philanthropist / Peter Melnycky -- The populist patriot: the life and literary legacy of Illia Kiriak / Jars Balan -- Sympathy for the devil : the attitude of Ukrainian war veterans in Canada to Nazi Germany and the Jews, 1933-1939 / Orest T. Martynowych -- Part three : Diplomacy and International Concerns -- The 'ethnic question" personified : Ukrainian Candians and Canadian-Soviet Relations 1917-1991 / Jaroslav Petryshyn -- Monitoring the 'Return to the homeland' campaign : Candian reports on resettlement in the USSR from South America, 1955-1957 / Serge Cipko -- Polishing the Soviet image : the Candian-Soviet Friendship Society and the 'progressive ethnics groups, ' 1949-1957 / Jennifer Anderson -- Part four : Internal Strife on the Left -- "Pop & Co' versus Buck and the 'Lenin School Boys' : Ukrainian Canadians and the Communist Party of Canada, 1921-1931 / Jim Mochoruk -- Fighting for the soul of the Ukrainian Progressive Movement in Canada : the lobayistes and the Ukrainian Labour-Farmer Temple Association / Andrij Makuch -- Part five : Everyday People -- 'Of course it was a communist hall' : a spatial, social, and political history of the Ukrainian Labour Temples in Ottawa, 1912-1965 / S. Holyck Hunchuck -- 'I'll fix you!' : domestic violence and murder in a Ukrainian working-class immigrant community in Northern Ontario / Stacey Zembrzycki -- Conclusion / Jime Mochoruk and Rhonda L. Hinther.
Includes bibliographical references and index.
English.
JSTOR
Keywords: Ukrainians -- Canada -- Social conditions -- 20th century; Ukrainians -- Canada -- History -- 20th century; Ukrainians -- Canada -- Etrhnic identity; HISTORY -- Canada -- General; HISTORY -- Canada -- Post-Confederation (1867- ); Ukrainians; Ukrainians -- Social conditions; Canada; 1900-1999; History